2019
DOI: 10.1186/s40561-019-0102-5
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of peer review as cooperative web-based learning method applied out-of-class in a role playing game: A case study by quasi-experimental approach

Abstract: Education at universities requires a high proportion of self-study supported by instruments which motivate students to deepen their knowledge with case studies and training software. The gain in learning is higher when what is learned is reflected by others in a cooperative process. The Class Peer Review (CPR) requires from students to evaluate each other but lecturers lose a lot of time when applying it during the lecture. Research on CPR shows many different approaches to how this method should be carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
1
4
0
1
Order By: Relevance
“…Hypothesis H-5 is therefore maintained. This is in line with current research literature, where Stark et al (2010) already noted a higher subjectively perceived group membership, but according to Friedrich (2019), Aziz and Hossain (2010) and Crowe et al (2015) the effect on performance in the exam is hardly pronounced. Obviously even a repeated review on the same topic could not change this.…”
Section: Effect Of the Review-design On The Basic Needs Variablessupporting
confidence: 92%
See 3 more Smart Citations
“…Hypothesis H-5 is therefore maintained. This is in line with current research literature, where Stark et al (2010) already noted a higher subjectively perceived group membership, but according to Friedrich (2019), Aziz and Hossain (2010) and Crowe et al (2015) the effect on performance in the exam is hardly pronounced. Obviously even a repeated review on the same topic could not change this.…”
Section: Effect Of the Review-design On The Basic Needs Variablessupporting
confidence: 92%
“…That a CPR has an effect on the variables of the Basic Needs has already been confirmed by the research literature, for example under Hossain and Tarmizi (2013). The author of the study on hand had already revealed the same in a study for an out‐of‐class application (Friedrich, 2019). Whether a significant change in the characteristics of the corresponding items actually took place as a result of the review‐design and whether this also had an effect on the knowledge test is now to be clarified.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…Следовательно, виртуальное И. Т. Мавродиева академическое общение и дистанционное обучение формируют знания и практический опыт. При организации тренингов, ролевых и симуляционных игр со студентами в будущем можно обсудить варианты включения экспертной оценки в качестве совместного веб-метода, который на практике является квазиэкспериментальным методом и описан Даниэлем Фридрихом (Friedrich 2019).…”
Section: обсуждение результатовunclassified